Fetal sigmoid colon mesentery made visible by routine ultrasound in the first and second trimester of pregnancy - Wozniak, Slawomir; Zazga, Maria; Kurc-Darak, Bozena; Tomialowicz, Marek; Paulsen, Friedrich; Florjanski, Jerzy (Annals of Anatomy-Anatomischer Anzeiger, 2021)
Background: Ultrasound is a routine procedure performed during pregnancy to monitor the status of the human fetus, including the development of the digestive tract. The aim of this publication was to determine the shape of the fetal sigmoid colon mesentery during the first and second trimester of pregnancy by means of ultrasound. Methods: The study was performed in 45 pregnant women (age: 36.4 years on average, range 25–45) during a routine ultrasound examination. The fetuses were between 12 and 22 weeks of pregnancy. The shape of the fetal sigmoid colon mesentery was analyzed. Results: We visualized the triangular shape of the mesentery in all 45 cases. A prevalence of scalene or isosceles acute triangles was found in both trimesters. At the 12−13 weeks we observed 5 different forms of mesenteric triangles – the scalene or isosceles acute triangles appeared at 33.3% and 28.6%, respectively. The obtuse scalene was present in 23.8 %. In the 2nd trimester (20−22 weeks) 4 types were found, among them 37.5 % acute scalene and 33.3 % acute isosceles. Conclusions: The fetal sigmoid colon mesentery can be visualized from the 12th week of pregnancy. The triangular shape of the sigmoid colon mesentery is easy to follow during routine ultrasound examinations.
CRIS-Team Scopus Importer:2021-02-19
Keywords: Fetal development; Fetal ultrasound; Human fetal sigmoid colon mesentery